Delay Causes Distribution: EU vs Croatian Coastal Airports - Bračić, Matija; Pavlin, Stanislav; Škurla Babić, Ružica (Promet - Traffic&Transportation, 2018)
The growth in air traffic in recent decades in Europe has consequently caused aircraft delays due to insufficient capacities of airspace and airports. Primary and reactionary delays at certain European and Croatian coastal airports in 2014 are analyzed in the paper according to CODA methodology and classified according to main flight delays causes. The largest share of delay minutes at the Croatian coastal airports (75%) are related to reactionary delays, ranging from around 20% to 60% of total delay at the most congested European airports. Special emphasis is given to the analyses of rotational reactionary delay, and the results indicate that the share of reactionary delay in total delay at the Split airport is significantly higher compared to selected European airports, which may be explained by delays propagated from air traffic network and limited airport capacity. The total recorded delay at Croatian coastal airports is minor compared to total recorded delay in the European air traffic system, but delay patterns are quite similar, especially during peak summer months.